The Role of Sacroiliac Joint Steroid Injections in the Treatment of Axial Spondyloarthritis - Serdar KOKAR,; Önder KAYHAN,; Savaş ŞENCAN,; Osman Hakan GÜNDÜZ, (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the effects of fluoroscopy-guided sacroiliac joint steroid injection in patients with acute bilateral sacroiliitis diagnosed with axial spondyloarthritis (axSpA) and how those injections affect the current need for nonsteroidal anti-inflammatory drug (NSAID) usage. Patients and methods: We retrospectively evaluated 43 patients (28 males, 15 females; mean age, 31.7±6.3 years; range, 18 to 44 years) fulfilling the Assessment of SpondyloArthritis international Society 2009 criteria for axSpA between June 2015 and May 2016. One group included 22 patients (injection group) treated with sacroiliac joint steroid injection (triamcinolone acetonide) and the other group included 21 patients (non-injection group) not receiving the injection. All 43 patients in both groups were treated with indomethacin peroral. Pre-treatment, first week and first, third and sixth month follow-up examinations were evaluated. Results: A ≥50% reduction in the numeric rating scale score compared with the baseline was considered as significant pain relief. The mean pain relief rates in patients receiving injections were higher at all inspections. This difference was statistically significant at first week (p<0.05). When groups were compared, no difference was found in the Bath Ankylosing Spondylitis Disease Activity Index scores (p>0.05). There was no statistically significant difference between the two groups when indomethacin dose was evaluated cumulatively for six months (p>0.05). Conclusion: Fluoroscopy-guided sacroiliac joint steroid injections can be recommended in patients with active sacroiliitis, particularly in those with severe axial pain, for rapid analgesia in the initial term. It was concluded that steroid injections applied to the sacroiliac joint did not affect disease activity. It is noteworthy that there is a trend to reduce the use of NSAIDs in patients receiving these injections, although it does not make a statistically significant difference in the long term.